2016
DOI: 10.1016/j.drugalcdep.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sweet flavorings and nicotine on the appeal and sensory properties of e-cigarettes among young adult vapers: Application of a novel methodology

Abstract: Introduction Product characteristics that impact e-cigarette appeal by altering the sensory experience of vaping need to be identified to formulate evidence-based regulatory policies. While products that contain sweet flavorings and produce a “throat hit” (i.e., desirable airway irritation putatively caused by nicotine) are anecdotally cited as desirable reasons for vaping among young adults, experimental evidence of their impact on user appeal is lacking. This experiment applied a novel laboratory protocol to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 16 publications
10
94
2
Order By: Relevance
“…In addition, surveys of ECIG users have demonstrated consistently that greater throat hit is associated with positive sensory effects such as overall device/liquid satisfaction and better taste (Etter, 2016;McQueen, Tower, & Sumner, 2011;Pokhrel, Herzog, Muranaka, & Fagan, 2015). However, in the present study higher ratings of "Throat Hit" did not coincide with more positive sensory effects and other experimental studies have demonstrated that throat hit is inversely associated with product satisfaction among young adult ECIG users (Goldenson et al, 2016). Because the 100PG:0VG liquid produced less positive sensory effects overall, the higher ratings of "Throat Hit" observed in this condition is likely another example of a negative sensory effect resulting from the use of this liquid.…”
Section: Comparison Of Mean (Sd) Nicotine Yield Results Fromcontrasting
confidence: 87%
“…In addition, surveys of ECIG users have demonstrated consistently that greater throat hit is associated with positive sensory effects such as overall device/liquid satisfaction and better taste (Etter, 2016;McQueen, Tower, & Sumner, 2011;Pokhrel, Herzog, Muranaka, & Fagan, 2015). However, in the present study higher ratings of "Throat Hit" did not coincide with more positive sensory effects and other experimental studies have demonstrated that throat hit is inversely associated with product satisfaction among young adult ECIG users (Goldenson et al, 2016). Because the 100PG:0VG liquid produced less positive sensory effects overall, the higher ratings of "Throat Hit" observed in this condition is likely another example of a negative sensory effect resulting from the use of this liquid.…”
Section: Comparison Of Mean (Sd) Nicotine Yield Results Fromcontrasting
confidence: 87%
“…Although average nicotine exposure between the usual and tobacco e-liquids were similar, the usual brand e-liquid was rated as more satisfying than the tobacco e-liquid, indicating that flavors play an important role in e-cigarette appeal. One study showed that while nicotine produces the throat-hit, it was the sweet flavors and not nicotine content that increased e-cigarette appeal (Goldenson et al, 2016). We did not see similar precise titration of nicotine exposure when we compared the strawberry flavor to the usual brand and tobacco e-liquids, respectively.…”
Section: 0 Discussionmentioning
confidence: 99%
“…We did not see similar precise titration of nicotine exposure when we compared the strawberry flavor to the usual brand and tobacco e-liquids, respectively. The perceived better taste of the strawberry flavor likely made it more appealing than the tobacco flavor, and hence greater consumption and nicotine exposure (Goldenson et al, 2016). …”
Section: 0 Discussionmentioning
confidence: 99%
“…In two of the studies, 121 young adult ECIG users (Study 1 n=101, Study 2 n=20; 57.5% current smokers) attended a single laboratory visit in which they self-administered experimenter-provided ECIGs (for details on the paradigm see Goldenson et al, 2016). In the other study, adult concurrent combustible cigarette and ECIG users (N=44) attended five visits in which they smoked their own preferred-brand cigarettes and used their own ECIGs.…”
Section: Methodsmentioning
confidence: 99%